The influence of human resource competence and motivation on work effectiveness at PT. Pupuk Kujang Cikampek - Inka Komalasari; Dadan Ahmad Fadili; Asep Maulana (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the effects of human resource competence and motivation on the work effectiveness of Junior Officer employees at PT Pupuk Kujang Cikampek. A quantitative research design employing descriptive and explanatory approaches was used. Data were collected through structured questionnaires administered to 134 Junior Officer employees and analyzed using multiple linear regression with SPSS 25. The findings indicate that human resource competence and motivation each have a positive and significant effect on work effectiveness. Competence contributes 6.14% to work effectiveness, while motivation contributes 13.50%, indicating that motivation exerts a stronger influence than competence. Simultaneously, both variables explain 29.7% of the variance in work effectiveness, with the remaining 70.3% attributable to other factors outside the scope of this study. These findings demonstrate that improving employee competence and strengthening work motivation are essential for enhancing organizational effectiveness. This study contributes to the human resource management literature by providing empirical evidence on the complementary roles of competence and motivation in improving employee work effectiveness and offers practical implications for organizations in designing integrated competency development and motivational strategies to enhance workforce performance. Keywords: Human Resource Competency; Motivation; Work Effectiveness; Pupuk Kujang Cikampek